Body control in media-normatizing politics: regularities in the 2002 Lula election campaign - doi: 10.4025/actascilangcult.v34i2.13966 - Elaine de Moraes Santos; Edson Carlos Romualdo (Acta Scientiarum. Language and Culture, 2012)
Body control in media-normalizing politics within the context of the Brazilian presidential candidate Luiz Inácio Lula da Silva’s electoral campaign in 2002 is analyzed and discussed. Photographs exhibited by three Brazilian weekly reviews, Época, IstoÉ and Veja, are analyzed according to French Discourse Analysis, mainly under the aegis of Foucault’s investigations. An analysis of the candidate’s photographic images reveals the social media’s concern in presenting Lula’s campaign through a representation featured by contrasting expositions. In fact, the 2002 election campaign is contrasted to that of former electoral periods. The normatization for a docile representation policy in the media comprises a regular ‘behavioral norm’ and a ‘gesture norm’when broadcasting Lula’s dociled body. The denunciation of body docilization by the social media also questioned the Brazilian Labor Party campaign as a possible de-characterization of Lula and his party to guarantee positive results in the elections. However, the historical review of body treatment and the contemporary overlaying of politics and the media show that the process of modifying Lula’s presidential campaign was an adaptation stance towards the needs of politics being more immersed in the communication media.